Kualitas Layanan dan Citra Lembaga terhadap Word Of Mouth Mahasiswa Stahn Gde Pudja Mataram - I Made Ngurah Oka Mahardika (Business Management Analysis Journal (BMAJ), 2020)
The competition between universities to get new students makes universities innovate in marketing strategy. This also applies to Sekolah Tinggi Agama Hindu Negeri (STAHN) Gde Pudja Mataram, a State Religious College under the Ministry of Religion continues to improve the service quality and company image so that students tell positive things to the community. This research used is quantitative method by taking 84 respondents of STAHN Gde Pudja Mataram bachelor students. The sampling technique uses accidental random sampling analyzed with SPSS 23 tools. The results of the analysis show that service quality has a positive but not significant effect on word of mouth. Then, the company image had a positive and significant effect on the word of mouth of STAHN Gde Pudja Mataram students. Therefore, STAHN Gde Pudja Mataram has to keep maintain the service quality and company image to the students so that they can raise the positive information by word of mouth to society.